Piezoelectric Nanomaterials for Cancer Therapy: Current Research and Future Perspectives on Glioblastoma - Zayne Knight; Amalia Ruiz; Jacobo Elies (Journal of Functional Biomaterials)
Cancer significantly impacts human quality of life and life expectancy, with an estimated 20 million new cases and 10 million cancer-related deaths worldwide every year. Standard treatments including chemotherapy, radiotherapy, and surgical removal, for aggressive cancers, such as glioblastoma, are often ineffective in late stages. Glioblastoma, for example, is known for its poor prognosis post-diagnosis, with a median survival time of approximately 15 months. Novel therapies using local electric fields have shown anti-tumour effects in glioblastoma by disrupting mitotic spindle assembly and inhibiting cell growth. However, constant application poses risks like patient burns. Wireless stimulation via piezoelectric nanomaterials offers a safer alternative, requiring ultrasound activation to induce therapeutic effects, such as altering voltage-gated ion channel conductance by depolarising membrane potentials. This review highlights the piezoelectric mechanism, drug delivery, ion channel activation, and current technologies in cancer therapy, emphasising the need for further research to address limitations like biocompatibility in whole systems. The goal is to underscore these areas to inspire new avenues of research and overcome barriers to developing piezoelectric nanoparticle-based cancer therapies.